Fundamental Approach for Analysis of Dynamic Characteristics of Fixtures - Vitalii Ivanov (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2018)
Present work is aimed at research of locating and clamping process of prismatic parts in fixtures during the machining on drilling-milling-boring machines. The fundamental approach for developing mathematical modeling of the system “fixture – workpiece” has been proposed. It allows to determine critical frequencies of functional elements oscillations and amplitude-frequency response characteristics, as well as dynamic component of fixture deformations at operating frequency of the machining process. The developed mathematical model is evaluated by numerical calculations of spectrum of critical frequencies considering the stiffness of cutting tool. The further researches are directed on the development of the methodology of calculation of the system “fixture – workpiece” by computer means of numerous realization and development of practical recommendations regarding its use during fixture design.